2020
DOI: 10.1089/caff.2019.0020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Caffeine Use Disorder Symptoms Among a United States Sample

Abstract: Background: The DSM-5 recognizes caffeine use disorder as a condition for further study, but there is a need to better understand its prevalence and clinical significance among the general population. Methods: A survey was conducted among an online sample of 1006 caffeine-consuming adults using demographic quotas to reflect the U.S. population. Caffeine consumption, DSM-proposed criteria for caffeine use disorder, sleep, substance use, and psychological distress were assessed. Results: Eight percent of the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…Feeling guilty or bad about caffeine use was associated with caffeine use disorder. Similar to the present study, depression, anxiety and stress were also reported to be more common in people with caffeine use disorder (37) .…”
Section: Discussionsupporting
confidence: 90%
“…Feeling guilty or bad about caffeine use was associated with caffeine use disorder. Similar to the present study, depression, anxiety and stress were also reported to be more common in people with caffeine use disorder (37) .…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown that IPEDs are increasingly bought over the Internet without any medical supervision, possibly leading to excessive or even toxic intakes (Mooney et al, 2017 ; Corazza et al, 2019 ). For example, the overuse of caffeine tablets could induce negative outcomes, such as insomnia or sudden death (Ronis et al, 2018 ; Booth et al, 2020 ; Sweeney et al, 2020 ), with caffeine use disorder being one of the conditions mentioned in the DSM-5 under a section on “Conditions for Future Study” (Ágoston et al, 2018 ). It is worth noting that in some cases, licit supplements themselves can contain undisclosed prohibited substances by the World Anti-Doping Agency (WADA) and thus expose users to unwanted health risks (Mazzoni et al, 2017 ; Helle et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] More recently, Sweeney et al reported that 8% of caffeine using individuals met criteria for DSM-5proposed Caffeine Use Disorder. 7 Almost all (95%) college students report daily caffeine consumption, with the average student consuming three to five times the daily recommended amount of caffeine (200-300 mg). 8 In particular, energy drinks (EDs) are heavily marketed to college students, and ED consumption has contributed to adverse health effects, prompting increased attention and cause for concern.…”
Section: Introductionmentioning
confidence: 99%